Holographic interferometry as a method to study conformational changes in macromolecules - Barabash, Y.; Kharkyanen, V.; Zabolotny, M.; Sokolov, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
This paper concerns with our measurements of reaction center (RC) volume changes in the course of photoactivation using the method of holographic interferometry. As a principal value, we studied changes of a solution refraction index (Δn) influenced by the sample volume expansion due to temperature changes (ΔnT), light absorption (Δnabs) and changes in the volume of photoactive molecules (DnV). Using the scheme of temperature compensation we could reduce the task to the case ΔnT <<Δnabs, ΔnV. At RC concentrations close to 10¹⁵ cm-³, our experimental setup enabled to register the shift of an interference pattern up to 0.1 of the bandwidth. Our estimations for the case of a protein solution yields in relative changes in the molecular volume within 10-³...10-².